School leavers' report - Trinidad and Tobago, Central Statistical Office (Central Statistical Office, 1977)
This publication provides data form a retrospective survey carried out during January-June 1973, as an attachment to the Continuous Sample Survey of Population. It aimed to cover persons between the ages of 15-24 years who left school during the period 1963-1972, and sought to gather information on their work experience after leaving school, such as the length of time taken to get their first job, the method of gaining employment, and the total time employed since leaving school. The sample consisted of 865 males and 898 females. Results of the data analysis indicated that: 1) between 1963 and 1967, there was little or no change in the labour force participation rate for school leavers, but from 1968 there was a significant increase in the rate for women; 2) since 1966, both male and female school leavers had made significant inroads into the professional and technical field, with small increases in the administrative, executive and managerial field, and a corresponding decrease in farming; and 3) from 1967, more women were leaving school at a later age.
Keywords: School leavers